Anorectal Malformations in Monozygotic Twins: An Illustration of Management of Anorectal Malformations in A Tertiary Hospital in Indonesia - Gunardi, Hardian; Rachmawati, Asri D; Susilo, Nanok E (UI Scholars Hub, 2021)
A case of monozygotic twin boys with anorectal malformation with delayed presentation of bowel perforation. Both are managed surgically with a colostomy; after a definite diagnosis of anorectal malformation with a urethral fistula based on distal colostography, both boys underwent anoplasty with a posterior sagittal approach. Stoma closure was performed, and we found no complication during eight months of follow-up. Delay in the management of the twins was due to a lack of anal screening of the newborn. The unavailability of the neonatal intensive care unit became a significant concern. Distal colostography was performed for the definitive procedure. Despite that limitation, anorectoplasty was performed with a posterior sagittal approach. Anorectal malformations in twins are a rare case requiring thoughtful surgical care. A thorough understanding of the limitation of our resources could help in planning management for anorectal malformation, especially in twins.